TAMSA Renaturalización de la Calle 26 (2022)
Bogotá, as the Capital District, has different systems of diverse complexity that are within the POT such as the socioeconomic, environmental, and functional structure. For this reason, different studies, plans and urban diagnoses have been carried out in order to improve the form and function of the city, this is the case of Avenida el Dorado, where the Rogelio Salmona Foundation has made a proposal on the street 26 where an ecological and cultural corridor is formed, from this proposal TAMSA begins to have an identity.